A Systematic Review on the Association Between Bilingualism and Theory of Mind in Adulthood - Rowena J. Xia; Brian W. Haas (Behavioral Sciences, 2025)
Previous research on the relationship of bilingualism and theory of mind has largely focused on children. However, several recent studies of the theory of mind have found differences in theory of mind processing among older populations, namely adults. Given that language has been found to play an important role in the successful theory of the mind task performance of adults, it is valuable to understand the relationship of the language ability of bilingualism and theory of mind in adults. The specific focus is on studies comparing monolinguals and bilinguals in a theory of mind assessment for an adult sample. In this systematic review, we reviewed and analyzed these studies and conducted a meta-analysis. Among the studies included for meta-analysis (k = 7), we found a significant small-to-medium effect size (d = 0.429, p < 0.0001), indicating a bilingual advantage among adults. A variety of different measures for theory of mind were included in these studies. More studies are required to better understand the relationship between multiple language processing and social cognition among adults to better understand this gap in the literature.